Analisis Bauran Pemasaran Terhadap Loyalitas Pelanggan Pada Apotek Mitra Farma Way Panji Lampung Selatan - Ratnasaria, Dewi; Saodin, Saodin (CV. ITTC INDONESIA, 2024)
Mitra Farma Way Panji Pharmacy has a level of competition that is starting to increase and maintain its business continuity, necessary to change consumers to become loyal customers. Considering that medicines are the the urgency of the need is high, so that the need for pharmaceutical products will increase along with the increase in the number of residents. This study significant influence of Products, Prices, Customer Loyalty Mitra Farma Way. This study research the sampling technique used is Non Probability Sampling with Accidental Sampling technique with a sample of 99 respondents. To find the Validity Test using r Product Moment, Test uses Cronbach Alpha. The results of this study show that Products have a significant effect on Customer Loyalty calculated value of 30,594> ttable 1,661 with a significance level of 0.000 < 0.05. Price has a significant effect on Customer Loyalty with a calculated value of 16,780> ttable 1,661 with a significance level of 0.000 < 0.05. Place has a significant Customer Loyalty calculated value of 3,742> ttable 1,661 with a significance level of 0.000 < 0.05 and Promotion has a significant Customer Loyalty with a calculated value of 28,051> ttable 1,661.